A feature-based representation of process planning and assembly knowledge for concurrent engineering applications - Wan Abdul Rahman Jauhari Bin Wan Harun; Keith Case (1999)
The need for a product model which can support the modelling requirements of a broad range of applications leads to the use of feature-based techniques. An important requirement in feature-based design and manufacture is that a single feature representation should be capable of supporting a number of different applications. Assembly and process planning are seen as two crucial applications and a formal structure for their representation in a feature-based design system is presented. This paper addresses two basic questions relating to the lack of a unified definition for features and the problem of representing assemblies in a feature-based representation. A prototype system has been implemented using object-oriented techniques which provide a natural method of adding functionality to the geometric reasoning process of features and the complex relationships between the parts that make up the assembly.